FACTORS AFFECTING PATIENT SATISFACTION HOSPITALIZATION OF FOOD SERVICE AT GRANDMED LUBUK PAKAM HOSPITAL - Delita Br Panjaitan; Achmad Rifai; Lilis Kurniawati (Fakultas Kesehatan Masyarakat Institut Kesehatan Medistra Lubuk Pakam, 2022)
Health services in hospitals consist of various parts, one of which is nutrition services. The hospital nutrition service program aims to improve the quality of hospital services by providing efficient and integrated nutrition services with other health services. Nutrition services in hospitals are part of supporting health services, namely part of medical therapy. This type of research is a quantitative research with an analytical survey with a cross sectional design which aims to determine the factors that influence inpatient satisfaction with food serving at Grandmed Lubuk Pakam Hospital. The population in this study were all inpatients at Grandmed Lubuk Pakam Hospital, which 256 patients were found based on an initial survey conducted in March 2022. The sample in this study were inpatients in the 3D room collected by 30 patients who were taken using the accidental sampling technique. Data collection uses primary data and secondary data. Primary data using a prepared questionnaire while secondary data obtained from the Medical Record section in the form of data on the number of inpatients at Grandmed Lubuk Pakam Hospital. After the data was processed using the chi square test at the 95% confidence level (? = 5%). The basis for decision making with the provision that if the value of p < then H0 is rejected which can be concluded that there is a relationship between the independent and dependent variables. Based on the results of the study, it is known that the factors that influence the level of satisfaction with the presentation of inpatients at Grandmed Lubuk Pakam Hospital, with an average result of 73.9%, (patients are satisfied